Nickel oxide (NiO) nanoparticles disturb physiology and induce cell death in the yeast Saccharomyces cerevisiae - Sousa, C. A. (2018)
The increasing use of nanoparticles (NPs) has spurred concerns about their toxic effects. This work aimed to assess the potential hazards of nickel oxide (NiO) NPs using the yeast Saccharomyces cerevisiae as a cell model. Yeast cells exposed for 6 h to 100 mg/L NiO NPs presented reduced metabolic activity (esterase activity and FUN-1 dye processing) and enhanced accumulation of reactive oxygen species. NiO NPs induced the loss of cell viability in a dose-dependent manner. Study of the dissolution of NiO NPs in aqueous media, together with the toxicological data, suggests that the nickel released by the NPs cannot explain all the toxic effects observed in S. cerevisiae caused by the NPs. Transmission electron microscopy observations revealed that NiO NPs were adsorbed onto cell surface but did not enter into yeast cells. Isogenic mutants (cwp1? and cwp2?) with increased cell wall porosity did not display enhanced susceptibility to NiO NPs compared to the wild type strain. Our results suggest that NiO NPs exert their toxic effect by an indirect mechanism. This work contributes to knowledge of the potential hazards of NiO NPs and to the elucidation of their mechanisms of toxic action.